2022
DOI: 10.1038/s41598-022-05394-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interferon-gamma-stimulated melanoma progression by targeting neuronal nitric oxide synthase (nNOS)

Abstract: Interferon-gamma (IFN-γ) is shown to stimulate melanoma development and progression. However, the underlying mechanism has not been completely defined. Our study aimed to determine the role of neuronal nitric oxide synthase (nNOS)-mediated signaling in IFN-γ-stimulated melanoma progression and the anti-melanoma effects of novel nNOS inhibitors. Our study shows that IFN-γ markedly induced the expression levels of nNOS in melanoma cells associated with increased intracellular nitric oxide (NO) levels. Co-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In vitro, we did not observe any significant difference in cytotoxicity between MAC-3-190 and co-administration of KK-11 and MAC-3-190 ( Figure 3 D). In addition, our previous studies and preliminary observations demonstrated that MAC-3-190 (5 mg/kg/day) does not have any significant antitumor activity in vivo [ 8 ]. Therefore, we evaluated if co-administration with KK-11 peptide would affect the antitumor activity of MAC-3-190 in vivo in mice carrying melanoma xenografts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro, we did not observe any significant difference in cytotoxicity between MAC-3-190 and co-administration of KK-11 and MAC-3-190 ( Figure 3 D). In addition, our previous studies and preliminary observations demonstrated that MAC-3-190 (5 mg/kg/day) does not have any significant antitumor activity in vivo [ 8 ]. Therefore, we evaluated if co-administration with KK-11 peptide would affect the antitumor activity of MAC-3-190 in vivo in mice carrying melanoma xenografts.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor size was measured with a caliper, and body weight was recorded once a week. When the tumor size reached approximately 800–1000 mm 3 , as calculated using the following formula: [Length × (Width 2 )]/2 (in mm) [ 8 ], mice were processed for in vivo or ex vivo imaging [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations